PENINGKATAN KEBERHASILAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DENGAN PENDEKATAN REFLECTIVE LEARNING - Khodijah, Nyayu (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2009)
The purpose of this study is to improve the success of PAI (Pendidikan Agama Islam or Islamic Education) instruction at Senior High School by developing a model of PAI instruction through the application of reflective learning approach. This study was carried out by using proactive action research method and intervention action model used by John Elliot. The data were collected and analyzed by using mixed method approach.The results showed that the performance of PAI instruction at Senior High School, which is indicated by the improvement of students’ religiosity, can be increased through the application of reflective learning approach. Moreover, the use of this reflective learning approach is also effective to increase the effectiveness, efficiency, and appeal of PAI instruction.